Construction and Application of VR / AR-based STEAM Curriculum System in Primary and Middle Schools under Big Data Background. Issue 3 (October 2020) - Hu, Xiaoqiang; Wang, Yuanyuan; Fan, Xiaoting; Ma, Zhimei
Abstract: Virtual Reality Technology has been widely used in teaching to provide learners with a real sense of learning experience. At the same time, the new educational models, such as STEAM education and Creator Education, which are strongly advocated by our country, combine the two and use visualized big data to screen and analyze STEAM education, to understand the connotation and application of STEAM education and the role of virtual reality technology in STEAM education. This paper expounds the goal and practical curriculum structure of STEAM curriculum system in primary and middle schools based on virtual reality technology, designs and integrates the curriculum structure, constructs the concrete curriculum system, and gives the thematic teaching organization form, finally, the teaching application of the course system is discussed.